2003
DOI: 10.1523/jneurosci.23-22-08125.2003
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Activation of NFAT (Nuclear Factor of Activated T-Cells)-Dependent Transcription: A Role for the Transcription Factor NFATc4 in Neurotrophin-Mediated Gene Expression

Abstract: A member of the neurotrophin family, brain-derived neurotrophic factor (BDNF) regulates neuronal survival and differentiation during development. Within the adult brain, BDNF is also important in neuronal adaptive processes, such as the activity-dependent plasticity that underlies learning and memory. These long-term changes in synaptic strength are mediated through alterations in gene expression. However, many of the mechanisms by which BDNF is linked to transcriptional and translational regulation remain unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
141
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 107 publications
(115 reference statements)
9
141
1
Order By: Relevance
“…Stimulation of cortical neurons with NMDA induced NFATc3 and NFATc4 nuclear translocation, although the time course of translocation was not examined (21). Treatment of hippocampal neurons with brain-derived neurotrophic factor also induced NFATc4 nuclear translocation that was independent of VGCC activity (47). Importantly, the rate and amplitude of NFATc4 nuclear translocation were not compared with that of other NFAT isoforms in these studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Stimulation of cortical neurons with NMDA induced NFATc3 and NFATc4 nuclear translocation, although the time course of translocation was not examined (21). Treatment of hippocampal neurons with brain-derived neurotrophic factor also induced NFATc4 nuclear translocation that was independent of VGCC activity (47). Importantly, the rate and amplitude of NFATc4 nuclear translocation were not compared with that of other NFAT isoforms in these studies.…”
Section: Discussionmentioning
confidence: 87%
“…Here, we describe the differential regulation of the two most commonly studied NFAT isoforms in neurons, NFATc3 and NFATc4 (5,6,20,21,23,(45)(46)(47)(48)(49)(50)(51). We find that although NFATc3 is rapidly dephosphorylated and translocates to the nucleus upon depolarization, NFATc4 remains phosphorylated and localized to the cytosol.…”
mentioning
confidence: 99%
“…The finding that NGF potentiates NFAT activation by attenuating NFAT kinase activity is novel, with previous studies having focused on the importance of a neurotrophin-induced increase in [Ca 2ϩ ] i for NFAT activation (15,28). Indeed, Groth et al (15,28) showed that another major neurotrophin, BDNF, activates NFAT-mediated transcription in hippocampal and spinal cord neurons and that these effects can be abolished by inhibiting either PLC or the endoplasmic reticulum Ca 2ϩ -ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that not only electrical activity and intracellular Ca 2ϩ , but also neurotrophins, in particular nerve growth factor (NGF), potently regulate NFAT function in neurons (4,15,28). For example, NGF and brainderived neurotrophic factor (BDNF) stimulate NFAT-dependent expression of inositol 1,4,5-trisphosphate receptor 1, BDNF, cyclooxygenase-2, and plasminogen activation inhibitor-1 in peripheral and central neurons (15,28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation